Calculation of optical properties of light-absorbing carbon with weakly absorbing coating: A model with tunable transition from film-coating to spherical-shell coating. (September 2018) - Kanngießer, Franz; Kahnert, Michael
Highlights: The linear depolarisation ratio and optical cross sections of soot aggregates covered with soluble material has been computed with two different models for two wavelengths, 355 and 532 nm. The speed of the transition from an aggregate covered with a thin film to one being encapsulated in a spherical shell is a key morphological feature affecting the linear depolarisation ratio. The resulting linear depolarisation ratios are consistent with existing lidar field measurements. Abstract: Optical properties of particles consisting of light-absorbing carbon (or soot) and a weakly absorbing coating material are computed at a wavelength of 355 nm and 532 nm. A morphological particle model is used, in which small amounts of coating are applied as a thin film to the surface of the aggregate, while heavily coated aggregates are enclosed in a spherical shell. As the amount of coating material is increased, a gradual transition from film-coating to spherical-shell coating is accounted for. The speed of this transition can be varied by specifying a single parameter. Two different choices of this parameter, corresponding to a slow and a rapid transition from film-coating to spherical-shell coating, respectively, are investigated. For low soot volume fractions the impact of this transition on the linear depolarisation ratio δl is most pronounced. The model that describes a rapid transition to a spherical coating yields results for δl that are more consistent with existing lidar field measurements than the slow-transition model. At 532 nm the relative uncertainty in modelled δl for a rapid transition values due to uncertainties in the aggregate's geometry and chemical composition are estimated to range from 109 to 243%, depending on the soot volume fraction. At 355 nm the relative uncertainties were estimated to range from 90.9 to 200%.